Prognosis of Guillain–Barré Syndrome Linked to COVID-19 Vaccination - Shaun Kai Kiat Chua; Qian Ying Soh; Seyed Ehsan Saffari; Eng-King Tan (Brain Sciences, 2022)
There have been increasing reports of Guillain–Barré syndrome (GBS), a rare but debilitating neurological disease, occurring post-COVID-19 vaccination. However, the outcomes and relationships between patient demographics and clinical outcomes of post-COVID-19 vaccination GBS remain unclear. To bridge this gap, our study investigates the outcomes and clinical factors associated with poorer GBS outcomes following COVID-19 vaccination. We conducted a review and pooled analysis of detailed data extracted from 57 published cases with the relevant search strategies and criteria. The groups compared included male versus female patients, 1st dose versus 2nd dose and early onset versus late onset of GBS. Multivariate regression analysis was performed to compare the vaccine type, clinical severity and post-treatment outcomes between these groups of patients. Our results highlight for the first time that females were significantly more likely to have severe clinical presentation and poorer outcomes compared to males. Additionally, viral vector vaccines were the predominant vaccine type administered in early-onset post-COVID-19-vaccination GBS and GBS occurring after the 1st vaccination dose. It was also shown that reported cases of post-vaccination GBS generally displayed a positive response to conventional treatment and had favourable post-treatment outcomes. Through this study, we have established important links and provided assuring evidence for treatment response and post-treatment outcomes of GBS occurring post-COVID-19 vaccination. While the COVID-19 vaccination brings about much greater benefits than risks, our findings provide further impetus for greater vigilance in certain patient groups and more studies to explore the mechanisms behind these links.